THE IMPLEMENTATION OF PROPHETIC IN INTERNALIZATION OF CHARACTER EDUCATION - Ubaidillah Wasi Ubaidillah; M Munif; Moh Izzuddin Mansyur (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
The aim of this research is to describe the implementation of three major projects (TPBs), which are conversions of prophetic values, namely humanization, liberation, and transcendence. The method employed in this study is qualitative with a descriptive approach. Data collection involves interviews, observations, and documentation. Data analysis includes data reduction, data presentation, verification, conclusion drawing, and for data validity, the Forum Discuss Group (FGD) technique is utilized. The results of this research indicate that the implementation of the three major projects (TPBs), which are conversions of prophetic values namely humanization, liberation, and transcendence are as follows: The value of transcendence is implemented through performing Dhuha prayers and reciting wirid; the value of liberation is implemented through sharing with others, social service, and charity; and humanization is implemented through caring for and teaching orphaned children, caring for the elderly, and participating in disaster relief efforts.